Novel spirocyclic tranylcypromine derivatives as lysine-specific demethylase 1 (LSD1) inhibitors. Issue 3 (5th January 2018) - Shi, Ying; Wu, Yan-Ran; Su, Ming-Bo; Shen, Dong-Hao; Gunosewoyo, Hendra; Yang, Fan; Li, Jia; Tang, Jie; Zhou, Yu-Bo; Yu, Li-Fang
Abstract : Herein we describe the design, synthesis, and biological evaluation of a novel series of tranylcypromine-based LSD1 inhibitors via conformational restriction using spiro ring systems. Abstract : Herein we describe the design, synthesis, and biological evaluation of a novel series of tranylcypromine-based LSD1 inhibitors via conformational restriction using spiro ring systems. A simple, direct spirocyclic analog of tranylcypromine (compounds8a and8b ) was shown to be a 28- to 129-fold more potent inhibitor of LSD1 enzyme compared to tranylcypromine. Further incorporation of various substituted benzyl groups to the amino group resulted in a suite of 2′, 3′-dihydrospiro[cyclopropane-1, 1′-inden]-2-amines that are potent LSD1 inhibitors with excellent selectivity profiles ( e.g. 14a, 15b, 16a, 19a and20b ) against closely related enzymes such as MAO-A, MAO-B, and LSD2.